2022
DOI: 10.3389/frvir.2022.957230
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of virtual reality for anatomic training during temporal bone dissection course

Abstract: Results: No differences were noted in the overall performance between the groups. However, participants with prior VR training had a lower mean time for surgical exposure of anatomical landmarks (antrum 22.09 vs. 27.64 min, p = 0.33; incus 60.00 vs. 76.00, p = 0.03; PSCC 71.83 vs. 88.50, p = 0.17) during dissection training. The participants considered VR beneficial for anatomy teaching, surgery planning, and training. Conclusion:This study demonstrated the feasibility of implementing VR training in a temporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Several studies have revealed that VRA considerably enhanced students' knowledge and skills in recognizing temporal bone structures (Timonen, Dietz, et al, 2022; Timonen, Iso‐Mustajärvi, et al, 2022). Another study discovered that VR training outperformed traditional approaches in enhancing students' three‐dimensional thinking abilities (Hou & Safwan, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed that VRA considerably enhanced students' knowledge and skills in recognizing temporal bone structures (Timonen, Dietz, et al, 2022; Timonen, Iso‐Mustajärvi, et al, 2022). Another study discovered that VR training outperformed traditional approaches in enhancing students' three‐dimensional thinking abilities (Hou & Safwan, 2023).…”
Section: Discussionmentioning
confidence: 99%